PERAN GURU TERHADAP PENINGKATAN MUTU PENDIDIKAN DI INDONESIA PADA MASA REVOLUSI INDUSTRI 4.0 - Ricky Mallisa; Angngel Rani (Jurnal Pendidikan (Teori dan Praktik), 2022)
The Industrial 4.0 revolution is a state and condition that fuels the physical and digital world. A holistic industrial 4.0 presence is connected to human life through sophisticated technological devices. This has also resulted in improved education in Indonesia, what we do know is that there will be many difficulties for teachers as drivers in the increasingly modern world in the industrial 4.0 environment. In regard to the issue, the authors would like to describe the role of the teacher that continues to exist as part of the industry’s implementation of education in Indonesia, by using qualitative research methods. The writer’s descriptive approach to collecting data in literature that explains how the objects written in this article relate. Then described in descriptive terms to express a new understanding. Of the study done in this text refers to describing world conditions for the industrial revolution, the condition of education in Indonesia during the industrial 4.0 revolution and the involvement of teachers and the actions that must be taken to improve education during the industrial 4.0 revolution.